2018
DOI: 10.1371/journal.pone.0193569
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial-based algorithm for insulin-pump therapy in hyperglycemic patients early after kidney transplantation

Abstract: Treating hyperglycemia in previously non-diabetic individuals with exogenous insulin immediately after kidney transplantation reduced the odds of developing Posttransplantation Diabetes Mellitus (PTDM) in our previous proof-of-concept clinical trial. We hypothesized that insulin-pump therapy with maximal insulin dosage during the afternoon would improve glycemic control compared to basal insulin and standard-of-care. In a multi-center, randomized, controlled trial testing insulin isophane for PTDM prevention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…In the early period after transplantation, insulin is the preferable choice of treatment, with life-style modification and oral anti-diabetic therapy being the next step in the consensus treatment algorithm [97]. Previous studies demonstrated that aggressive anti-hyperglycaemic therapy with insulin, early (<3 weeks) after kidney transplant, lowered the risk for developing PTDM after 1 year [98] and the results of a following study, ITP-NODAT, using insulin pump technology to treat NO-DAT, is expected [99]. Both recent and ongoing trials on PTDM are depicted in Table 2.…”
Section: Treatment Of Established Ptdmmentioning
confidence: 99%
“…In the early period after transplantation, insulin is the preferable choice of treatment, with life-style modification and oral anti-diabetic therapy being the next step in the consensus treatment algorithm [97]. Previous studies demonstrated that aggressive anti-hyperglycaemic therapy with insulin, early (<3 weeks) after kidney transplant, lowered the risk for developing PTDM after 1 year [98] and the results of a following study, ITP-NODAT, using insulin pump technology to treat NO-DAT, is expected [99]. Both recent and ongoing trials on PTDM are depicted in Table 2.…”
Section: Treatment Of Established Ptdmmentioning
confidence: 99%
“…Despite increased awareness of NODAT and complications early post-transplant, there is no consensus on treatment or therapies ( 29 ). Carbohydrates (CHO) contribute the highest amount of energy in the typical American diet, making up 50% of total kilocalories from a recent report from 2007 to 2012 NHANES data ( 12 ).…”
Section: Macronutrientsmentioning
confidence: 99%
“…In non-diabetic KTRs participating in a randomized controlled trial assessing the effectiveness and safety of continuous subcutaneous insulin lispro infusion (CSII, presupper BG target 110 mg/dL) as compared to basal insulin treatment (pre-supper BG target 110 mg/dL) and standard therapy (i.e. short-acting insulin lispro aiming at pre-lunch and pre-supper blood glucose values < 200 mg/dL), CSII resulted in significantly lower blood glucose levels during the first week after kidney transplantation, as compared to a basal insulin isophane regimen and to standard therapy for most time points [68]. However, longer term results of this study have not been published yet.…”
Section: Insulin Therapymentioning
confidence: 99%